Oral history association of Malaysia : programmes, issues and challenges / Zahidi Zainol Rashid - Rashid, Zahidi Zainol (Faculty of Information Management, 2013)
The Oral History Association of Malaysia was formed in order to gather information based on oral history approaches and to promote this information sources as an important material for research on history in the near future. Historical records of an event can be completed through oral history since part of the information still resides in a person's memory. Interview is one method that is used in oral history to collect information from an individual. Evidence shows that not all documented records are thorough and adequately recorded. Gaps still exist in history. It is within this context that Oral History Association of Malaysia will help to fill gaps that exists particularly in historical events. Many institution are involved in oral history activities which were carried out by full-time and part-time staff as well as students. Among the issues and challenges faced were "the race against time/'the high cost of conducting an oral history project choice and scope of the topic chosen, authenticity of material collected.